Perbedaan Jenis Tanah dan Umur Tanaman Terhadap Produksi Tandan Buah Segar Kelapa Sawit (Elaeis guineensis Jacq): Differences in Soil Type and Plant Age on the Production of Fresh Fruit Bunch of Oil Palm (Elaeis guineensis Jacq) - Muhammad Riskar; Ahkmad Sopian (Universitas Widya Gama Mahakam, 2024)
This research was conducted in the area of PT. Sawit Sukses Sejahtera and PT. Prima Cipta Selaras, Muara Ancalong District, East Kutai Regency, East Kalimantan Province. The time period for 4 months of research was carried out in April 2019 until August 2019. The purpose of this study was to determine the test of differences in plant age and land characteristics on oil palm productivity. The research method using the field survey method was analyzed using a variety of non factorial randomized block designs. The results showed that differences in plant age had no significant effect on average longitudinal weight but had a significant effect on the average number of flowers and flowers, the highest value at 9 years of age was 7.3 long / principal and the lowest at 8 years of age was 4.1 length / the principal. In soil type, it has no significant effect on the average number of lengths and flowers, but has a very significant effect on average length weight in Ultisol soil types having the highest average length weight of 14.2 kg / length and the lowest in spodosol soil types, 8.7 Kg / long. In the type of flat topography and hill has no significant effect on the average number of lengths and flowers but has a significant effect on the average long weight, on the flat topography has the highest weight of 15.28 kg / long and on the topography of the hill which is 8.47 kg / length.